2018
DOI: 10.1177/0894439318779145
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for “Liking” on Social Networking Sites

Abstract: The “ like” feature is popularly utilized by online social media users for different reasons including socializing, giving feedback and giving or seeking attention as well as for pure affection. The “ like” function is a gamified element of social networking sites used billions of times per day. Despite its widespread use in the social media space, little is known about the different factors that influence Facebook users’ “ like” continuation intention or the game mechanics of “ like.” To address this relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…In this sense, it is important to bear in mind that excessive browsing through social networks can limit the oral communication of young people [74]. However, encouragingly, it seems that although self-efficacy is associated with greater use of technology and social networks [22], it is not associated with greater exposure of personal images on social networks [76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, it is important to bear in mind that excessive browsing through social networks can limit the oral communication of young people [74]. However, encouragingly, it seems that although self-efficacy is associated with greater use of technology and social networks [22], it is not associated with greater exposure of personal images on social networks [76].…”
Section: Discussionmentioning
confidence: 99%
“…Gender and age also influence the degree of self-efficacy, since studies have demonstrated that there are differences in this at the academic, social, and sports levels [21]. In adolescents, self-efficacy and performance expectations are linked to greater use of technology and social networks [22]. In university students, self-efficacy is linked to all dimensions of psychological well-being such as self-acceptance, environment domain, purpose in life, personal growth, autonomy, and positive relationships [23], as well as a higher degree of employment [24] and to future job prospects [25].…”
Section: Perceived Academic Self-efficacymentioning
confidence: 99%
“…In the current environment of robust SNS research, U&G theory has extensively explored the reasons for individuals' use of different SNSs including Facebook [2,18], WeChat [7], Twitter [19], social virtual worlds [10], and social networking games [12,20] (see Table 1). Table 1 summarizes the major findings of studies on U&G theory in the SNS context.…”
Section: Uses and Gratification Theorymentioning
confidence: 99%
“…It has been suggested that the theory of uses and gratifications (U&G) may be useful to predict the liking behavior of WeChat users [7]. Social presence, primary and secondary influence, habit and self-efficacy significantly affect Facebook "like" continuation [12]. While some research has explored SNS liking behavior in terms of U&G theory, subjective norm approaches have been overlooked in the SNS context.…”
Section: Introductionmentioning
confidence: 99%
“…The TPB is a popular social–psychological framework that has been widely used for understanding and explaining human behavior in the computer-mediated communication environment (Carter & Yeo, 2016; Cheung & To, 2016; Dhir, Khalil, Kaur & Rajala, 2018; Jiang et al, 2016; E. Kim, Lee, Sung, & Choi, 2016).…”
Section: Introductionmentioning
confidence: 99%